Striving to integrate self-management into daily life: a qualitative meta-synthesis of the perspectives and experiences from head and neck cancer survivors - Hao Zhang; Li Yin; Qing Yang; Aiping Wang; Linyu Xu; Jianxia Lyu (BMJ Open)
Background Head and neck cancer (HNC) represents a prevalent category of malignant tumours, with disease-associated and treatment-associated symptoms often resulting in significant complications that adversely impact patient quality of life. Effective self-management during treatment and rehabilitation is crucial for mitigating or delaying the onset of these symptoms. While existing studies have investigated various aspects of self-management, including its content, influencing factors and specific strategies for managing symptom burden in HNC survivors, no comprehensive study of the self-management experience in this patient population has hitherto been conducted.Objective This study aimed to systematically synthesise evidence on the content, experiences, barriers and facilitators of self-management among patients with HNC, with the ultimate goal of informing tailored self-management interventions.Design A systematic review of qualitative studies was conducted using a meta-aggregation approach.Methods A three-step search strategy was implemented to systematically review eight databases, including PubMed, Web of Science, CINAHL and Embase, from inception to June 2024. This review concentrated on studies examining the content of self-management for patients with HNC during treatment and rehabilitation, identifying both facilitators and barriers and delineating empirical self-management strategies. Two researchers independently screened the literature and performed quality assessments using the Joanna Briggs Institute qualitative research evaluation tool. Subsequently, data extraction was conducted to collect pertinent information. This qualitative systematic review adheres to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and the Enhancing Transparency in Reporting the Synthesis of Qualitative Research statement.Results A total of 3263 studies were identified, of which 15 met the inclusion criteria and were subsequently incorporated into the meta-synthesis. This integration revealed 3 primary themes and 10 subthemes, specifically: (1) the management of disease-related and treatment-related symptoms and functional alterations in HNC, exploring self-management strategies such as coping with and monitoring physical and mental symptoms and adjusting to modifications in fundamental operations; (2) barriers and facilitators in the integration process of self-management, including psychological, emotional and cognitive disorders, the impact of symptom burden on patients’ motivation and capacity for self-management, structural impediments and facilitators; and (3) challenges in incorporating self-management into daily life and strategies for effective implementation, encompassing acceptance and adaptation as strategies for coping and thriving, proactive issue resolution, self-motivation and the employment of a diverse array of targeted strategies emphasising recovery.Conclusions Patients diagnosed with HNC must engage in extensive self-management throughout diagnosis and treatment, encountering numerous challenges when integrating self-management practices into their daily lives. Despite the numerous challenges encountered, patients with HNC continue to endeavour to incorporate self-management strategies into their daily routines. Future research could leverage these insights to further investigate and delineate the essential elements and effective components of self-management and design targeted self-management interventions tailored for this patient population.PROSPERO registration number CRD42022365704.